Lynx canadensis Kerr 1792 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lynx canadensis Kerr, 1792. Anim. Kingdom, 1:155. TYPE LOCALITY: Eastern Canada (= Quebec). DISTRIBUTION: Taiga zone of North America, south to C. Utah and S.W. Colorado, N.E. Nebraska, S. Indiana, and N. Virginia (U.S.A.). COMMENT: Included in F. lynx by Corbet, 1978:183, but given specific status by Matyushkin, 1979, Arch. Zool. Mus. Moscow St. Univ., 18:76-162; and Werdelin, 1981, Ann. Zool. Fenn., 18:37-71. PROTECTED STATUS: CITES - Appendix II as Felidae. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 281, DOI: 10.5281/zenodo.7352980